Low-dose intravenous esketamine on a depressive catatonia patient with venous thromboembolism: a case report - Zhang, Meng-han; Wang, Yi-fan; Li, Juan; Liu, Zi-jun; Ji, Xiao (Frontiers in Psychiatry, 2025)
BackgroundCatatonia is a rare but potentially life-threatening psycho-motor syndrome. It is mainly manifested as decreased activities, or excessive and specific activities, such as stupor, agitation and defiance. Catatonia can appear in various diseases and the diagnosis and treatment of depressive catatonia are often delayed. As an N-methyl-D-aspartate (NMDA) receptor antagonist, esketamine shows antidepressant and anti-catatonic effects by regulating glutamatergic signal transduction and enhancing synaptic plasticity.MethodsThe present case involved a 55-year-old woman with depressive catatonia. Benzodiazepines, aripiprazole and nutritional support were given after admission. As she had a poor response to the initial treatment, we considered using the modified electroconvulsive therapy (MECT). Due to the deep vein thrombosis in the lower extremities, the application of MECT was restricted. With the consent of her and family, we decied to administrate a sub-anesthetic dose of intravenous (IV) Esketamine (0.2 mg/Kg) combined with 50mg desvenlafaxine. During the process, we assessed the effect by comparing depression severity scores using validated psychiatric scales before and after the treatment. Adverse drug reactions were evaluated by adverse drug reaction scale.ResultThe symptoms of catatonia were relieved in 4 hours after esketamine administration. The Bush-Francis Catatonia Rating Scale (BFCRS) decreased from 19 to 0. 48 hours after injection, the depressive symptoms were relieved and the Montgomery Åsberg Depression Rating Scale (MADRS) decreased from 46 to 9. The condition remained stable on 20 weeks of follow-up.ConclusionsAs a safe and rapid intervention, Esketamine might be a new option for catatonic patients who cannot undergo MECT or fail to respond to conventional treatment. It may be worthy of further research in the future.